SEX IDENTIFICATION OF DATE PALM BY USING DNA MOLECULAR MARKERS - & et al., Khierallah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted to investigate the early detection of date palm gender, the current study was conducted using some DNA markers technology using Bulk Segregant Analysis (BSA) and three molecular markers including Randomly Amplified Polymorphic DNA (RAPDs), and Cleaved Amplified Polymorphic Sequence (CAPS) and Nested PCR. Results showed that RAPD primers used cleared different banding pattern. Fifty primers showed monomorphic bands while ten showed polymorphic bands for the two balks Males (MB) and females (FM). These primers showed 626 total bands in which 41 of them was polymorphic (6.54% polymorphism). OPD.10 primer gave the highest number of bands reached 118 bands and was the highest efficiency (18.85%). While the primer OPE04 was least efficient (3.51%), giving only 22 bands. A band with molecular weight of 143 bp appeared in six females of the total seven female varieties (85.71%) and did not appear in all males suggesting a positive marker which could be consider a candidate region for gender in date palm. Results of CAPS markers using three restriction enzymes: Bcl I, Hpa II and RsaI to digest the PCR products of OPD.10 primer. Results indicated that not all enzymes were useful for cutting DNA of samples. Bcl I enzyme cut the band of 143 bp which appeared in six female samples, while Hpa II enzyme cut the band of 180 bp in five males and six females. The former enzyme had also cut and the band of 433 bp in all female varieties. No response was noted when DNA was restricted with enzyme RsaI. The above results consider to be promising for gender detection in date palm.